STUDI TENTANG NILAI-NILAI PANCASILA YANG TERKANDUNG DALAM UPACARA ADAT PERKAWINAN MASYARAKAT PETALANGAN DI KECAMATAN BANDAR PETALANGAN KABUPATEN PELALAWAN - Yurnalis, Afrizal; Arianto, Jumili; ', Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research background Pancasila as the outlook of the nation ofIndonesia, Pancasila because in essence is not only a result of contemplation thinkingperson or group of persons as the ideologies that exist in the world. However Pancasilavalues extracted from the customs, cultural values and religious values contained in theIndonesian nation. As well as the implementation of the Community PerkawiananPetalangan Ceremony in District Bandar Petalangan Pelalawan are carried down fromgeneration-kegenari. Formulation of the problem in this study is whether embodied thevalues of Pancasila in Petalangan Community Marriage Ceremony in District BendarPetalangan Pelalawan. The purpose of this study was to determine the values ofPancasila contained in Petalangan Community Marriage Ceremony in District BandarPetalangan Pelalawan. The population in this study is the whole community that theDistrict Bandar Petalangan been doing weddings. While the sampling techniquemenggunanakan purposive sampling technique as many as 50 people from 4,038families who have been married. Data collection techniques used in this research thatuse traditional questionnaires, interviews and document as well. Data analysistechniques used in this research is descriptive quantitative by using the formula P = F /n x 100%. The results showed (6) the dominant indicator that there nilia Pancasilavalues with the average percentage of respondents to answer "Yes" for (91.47%), and(6) other less dominant indicator that there are values of Pancasila with the averagepercentage of respondents to answer "Yes" for (79.33%). So it can be totaled from 50the percentage of respondents who stated that there are values of Pancasila inCeremony Perkawianan Petalangan Society at (85.4%), including the benchmarks"Yes" is between 50.01% -100%. So in this study proved that Petalangan CommunityMarriage Ceremony in District Bandar Petalangan Pelalawan contains the values ofPancasila.Keywords: Values Pancasila, Petalangan Community Marriage Ceremony